Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration and mineral salts and vitamins, which keep our bodies in good order and protect us from disease. Without using scientific terms, a healthy diet may be described as an abundant and varied diet of quite ordinary foodstuffs — the kind of diet the housewife tries to provide when she can afford it. She knows that her family require a fair amount of “filling” things — bread, potatoes, cereals, which satisfy hunger, and which, along with fats, are the sources of warmth and energy: that they need a reasonable quantity of body-building food like milk, cheese, eggs, fish and meat. She also knows that fresh natural foods should have an important place in the diet — e.g., milk; eggs, fresh fruit and vegetables and fat fish, in addition to other uses they may have, contain the vitamins which are so essential for health and growth; green vegetables and eggs supply iron which is necessary to make blood; milk and eggs provide calcium and phosphorous, which are needed to build teeth and bones. Medical investigation has shown very clearly that there is a close connection between diet and the proper development of bones, teeth and tissue, and the proper functioning of the body; that the right diet is a means of preventing rickets, anaemia and other “deficiency” diseases; that a right diet is all-important for expectant and nursing mothers, infants and children, if the health of the adult is to be sound. It has also been shown that where a proper diet is lacking, it is impossible to derive advantage from other factors — e.g., improved housing — which normally make for better health. MINIMUM versus “OPTIMUM” STANDARDS While there is general agreement among the experts as to what foods are essential and why, and what is likely to happen to us if we have to go without them, they approach the problem of diet from different angles. Some of the Nutrition inquirers attempt to discover the minimum diet on which health can be maintained — the diet below which it would be dangerous to fall — (e.g., The Report of the British Medical Association Committee on 8 127/NU/5/5/1/12